Projected Volume of Primary Total Joint Arthroplasty in the U.S., 2014 to 2030. (5th September 2018) - Sloan, Matthew; Premkumar, Ajay; Sheth, Neil P.
Abstract : Background: The volume of primary total joint arthroplasty (TJA) procedures has risen in recent decades. However, recent procedure growth has not been at previously projected exponential rates. To anticipate the future expense of TJA, updated models are necessary to predict TJA volume in the U.S. Methods: Retrospective review using the National Inpatient Sample, a representative sample of all hospital discharges within the U.S., was employed to determine the volume of primary TJA procedures performed from 2000 to 2014. Over 116 million discharge records were reviewed and weighted to determine the simulated annual TJA volume. The annual incidence rate of each procedure was determined by combining procedure volume with annual census data among the overall population and in subpopulations defined by sex and age. Linear and Poisson regression analyses were performed to determine the projected future volume of TJA procedures. Subanalysis with linear regression estimates based on 2000 to 2008 and 2008 to 2014 growth rates was performed. Results: On the basis of 2000-to-2014 data, primary total hip arthroplasty (THA) is projected to grow 71%, to 635, 000 procedures, by 2030 and primary total knee arthroplasty (TKA) is projected to grow 85%, to 1.26 million procedures, by 2030. However, TKA procedure growth rate has been slowing over recent years, and models based on 2008-to-2014 data projected growth to only approximately 935, 000 procedures by 2030. Conclusions: Previously anticipated exponential TJA growth is inconsistent with the most recent trends. An updated projection based on 2000-to-2014 data is provided to project the growth of primary TJA procedures to the year 2030. These data will help guide health-care economic policy and allocation of future resources in order to optimize the delivery of patient care.